Directly monitor protein rearrangement on a nanosecond-to-millisecond time-scale - Eric H.-L. Chen (Nature Portfolio, 2017)
Abstract In order to directly observe the refolding kinetics from a partially misfolded state to a native state in the bottom of the protein-folding funnel, we used a “caging” strategy to trap the β-sheet structure of ubiquitin in a misfolded conformation. We used molecular dynamics simulation to generate the cage-induced, misfolded structure and compared the structure of the misfolded ubiquitin with native ubiquitin. Using laser flash irradiation, the cage can be cleaved from the misfolded structure within one nanosecond, and we monitored the refolding kinetics of ubiquitin from this misfolded state to the native state by photoacoustic calorimetry and photothermal beam deflection techniques on nanosecond to millisecond timescales. Our results showed two refolding events in this refolding process. The fast event is shorter than 20 ns and corresponds to the instant collapse of ubiquitin upon cage release initiated by laser irradiation. The slow event is ~60 μs, derived from a structural rearrangement in β-sheet refolding. The event lasts 10 times longer than the timescale of β-hairpin formation for short peptides as monitored by temperature jump, suggesting that rearrangement of a β-sheet structure from a misfolded state to its native state requires more time than ab initio folding of a β-sheet.